2020
DOI: 10.1108/idd-04-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Applying social media to environmental education: is it more impactful than traditional media?

Abstract: Purpose This study aims to explore how social media help promote environmental education and pro-environmental behaviours by analysing how young adults access social media and traditional media to obtain environmental information differently, how environmental ideas are disseminated through social media and how people perceive and realise environmentalism. Design/methodology/approach This is a qualitative study based on a semi-structured interview with student participants. The questions used in the intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Green technology is also an important topic nowadays (Chung et al, 2020;Guleria and Kaur, 2021;Ho et al, 2022a,b). Soroya et al (2022)…”
Section: Use Of Augmented Reality (Ar) and Visual Technologies For Di...mentioning
confidence: 99%
“…Green technology is also an important topic nowadays (Chung et al, 2020;Guleria and Kaur, 2021;Ho et al, 2022a,b). Soroya et al (2022)…”
Section: Use Of Augmented Reality (Ar) and Visual Technologies For Di...mentioning
confidence: 99%
“…According to Lee (2014), “The importance of social networks in consumer decision-making and the behavior of the research community is very high.” Therefore, faculty members and academic libraries need to pay special attention to social networks in scientific activities and course works. This point is pointed up by Chung et al (2020) as well. They suggested to curriculum developers and instructors to consider the usage of social media to augment classroom activities and discussions.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, quantitative and survey studies have limitations that can be overcome through qualitative studies. Accordingly, it is highly suggested that future works examine the behavior of information seeking and faculty members' use of the internet, databases and online social networks, focusing on qualitative approach and methods, such as study of Chung et al (2020) and Williams et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, researchers can get more real first-hand information to support their own research. On the other hand, we are also interested in privacy-related issues (Hung et al , 2007) and applying social capital theories in education aids through social networks (Chung et al , 2020; Fong et al , 2020).…”
Section: Discussionmentioning
confidence: 99%